2010
DOI: 10.1177/0363546510384787
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Predictors of Intra-articular Hip Disease in Arthroscopy

Abstract: Several clinical and radiographic characteristics--most notably, male sex, older age, Tönnis grade, and elevated alpha angle--are associated with more severe intra-articular hip disease. The recognition of these associations between clinical and radiographic characteristics and hip disease patterns is important for patient selection, surgical planning, and patient counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
125
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(140 citation statements)
references
References 47 publications
13
125
1
1
Order By: Relevance
“…Several articles have used Tönnis grade as a descriptive for outcome studies [6,9,13,15,16,22,25]. One recent article excluded patients with Tönnis Grade 2 or greater and greater than 50% narrowing of the joint space and still had 8% conversion to THA [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles have used Tönnis grade as a descriptive for outcome studies [6,9,13,15,16,22,25]. One recent article excluded patients with Tönnis Grade 2 or greater and greater than 50% narrowing of the joint space and still had 8% conversion to THA [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [14,15] show a relationship between the Tönnis grade on plain radiographs and the presence of cartilage lesions in the hip at time of surgery. A recent study [13] with a 10-year followup of hip arthroscopy showed the grades of cartilage lesions noted at the time of surgery were predictors of THA.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that younger patients with no or mild preoperative arthritis have better functional outcome [7], this is the first radiographic predictor of postoperative function to our knowledge. Higher alpha angles have been shown to be associated with cam-type femoroacetabular impingement (FAI) [3,4,13,20]. A recent study by Albers no offset correction in a nonspherical femoral head PAO = periacetabular osteotomy; CEA = center-edge angle; OA = osteoarthritis; LCE = lateral center-edge.…”
Section: Discussionmentioning
confidence: 99%
“…As the concept of femoroacetabular impingement (FAI) has become accepted [23], more hip problems are being treated with joint preservation surgeries [5,46,61]. These advances in hip preservation are fueled by better diagnostics and technical improvements in both hip arthroscopy Each author certifies that he or she, or a member of his or her immediate family, has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of focal cartilage lesions caused by FAI are located on the acetabulum [23,46,62], although femoral head defects are not infrequent [40,54]. Acetabular cartilage defects are often treated by débridement of loose flaps, rim trimming, and microfracture of the remaining defect.…”
Section: Introductionmentioning
confidence: 99%